Asociación entre funcionalidad familiar y violencia adolescente en estudiantes de una institución educativa urbana, 2024 - Wilhelm Jimenez, Johnny Stanley (2023)
There is a gap in knowledge about the relationship between family violence and adolescent violence in our locality. Violence in the home has been found to be associated with psychological and behavioral problems that increase the risk of adolescents engaging in violent acts. However, it is not known how this dynamic specifically affects our community, making it difficult to implement effective prevention and management strategies. The objective of this work is to determine the association between family functionality and adolescent violence in students of an urban educational institution, 2023. For this reason, an observational-analytical and prospective study was developed, with a sample of 132 students. Among the results, it was observed that 69.7% of adolescents reported having experienced some type of violence. In relation to family functionality, it was observed that 36.4% of the respondents had a dysfunctional family. Finally, it was concluded that family functionality is related to adolescent violence (p=0.029), and that adolescents from dysfunctional families are 2.5 times more likely to experience adolescent violence than those from functional families. These findings highlight the importance of addressing family functionality as part of interventions aimed at preventing and reducing adolescent violence in our town.